Using soil and canopy temperature to support efficient management of irrigated vineyards - Costa, J. M. (2020)
Extreme heat and drought events are becoming more frequent and erratic in Mediterranean Europe. Better comprehension of spatial and temporal dynamics of heat fluxes and thermal microclimate in vineyards can support vineyard’s management and minimize the impact of climate variability. Field experiments were carried out in South Portugal with two red cvs. Touriga Nacional and Aragonez (syn. Tempranillo) under deficit irrigation. Canopy temperature (Tc) is a robust predictor of plant water status, especially when measured under more stressful conditions. In parallel, soil temperature (TS) had a positive influence on TC especially at the cluster zone